De la spécificité du concept de santé environnementale vis-à-vis du développement durable - Julien Forbat (Développement Durable et Territoires)
This article proposes a study of the concept of environmental health and of its links with sustainable development. Whereas both concepts have had distinct historical courses, since the end of the 1980’s we are witnessing a strong connection resulting mainly in the attempt to integrate the concept of environmental health and that of sustainable development. However, these two concepts, even though they share some common characteristics, still remain basically different. Consequently, this article aims at reformulating the concept of environmental health and its relationship to sustainable development, in order to give it more autonomy.